Distinguishing Rapid and Slow C Cycling Feedbacks to Grazing in Sub-arctic Tundra - Ylänne, Henni; Stark, Sari (Ecosystems, 2019)
Large grazers are known to affect ecosystem functioning even to the degree where ecosystems transition to another vegetation state. Alongside the vegetation change, several features of ecosystem functioning, such as ecosystem carbon sink capacity and soil carbon mineralisation rates, may be altered. It has remained largely uninvestigated how the grazing effects on carbon cycling processes depend on the duration of grazing. Here, we hypothesised that grazing affects ecosystem carbon sink through plant-driven processes (for example, photosynthesis) on shorter time-scales, whereas on longer time-scales changes in soil-driven processes (for example, microbial activity) become more important contributing to a decreased carbon sink capacity. To test this hypothesis, we investigated key processes behind ecosystem carbon cycling in an area that recently had become dominated by graminoids due to a high reindeer grazing intensity and compared these to the processes in an area of decades old grazing-induced graminoid dominance and in an area of shrub dominance with little grazer influence. In contrast to our hypothesis, areas of both old and recent grassification showed a similar carbon sink capacity. Yet the individual fluxes varied depending on the time passed since the vegetation shift: ecosystem respiration and mid-season photosynthesis were higher under old than recent grassification. In contrast, the extracellular enzyme activities for carbon and phosphorus acquisition were similar regardless of the time elapsed since grazer-induced vegetation change. These results provide novel understanding on how ecosystem processes develop over time in response to changes in the intensity of herbivory. Moreover, they indicate that both autotrophic and heterotrophic processes are controlled through multiple drivers that likely change depending on the duration of herbivory.